748 views
0 votes
X^2+12x=-36 solve for x

User Userxxx
by
5.6k points

2 Answers

4 votes

Answer:

x = -6 (multiplicity 2)

Explanation:

x^2 + 12x = -16.

Rearranging:-

x^2 + 12x + 36 = 0

We can factor this. Note +36 = +6 * +6.

So (x + 6)(x + 6) = 0

x = -6 (multiplicity 2).

User Admit
by
5.1k points
3 votes

Answer:

x = - 6

Explanation:

rearrange into standard form : ax² + bx + c = 0 : a ≠ 0

add 36 to both sides

x² + 12x + 36 = 0 ← in standard form

(x + 6)(x + 6) = 0 ← in factored form

(x + 6)² = 0, hence

x + 6 = 0 ⇒ x = - 6



User TheSalamov
by
5.0k points